Antimicrobial resistant and extended-spectrum ß-lactamase (ESBL) producing Escherichia coli isolated from fecal samples of African dromedary camels - Nüesch-Inderbinen, M.; Kindle, P.; Baschera, M.; Liljander, Anne M.; Jores, Joerg; Corman, V.M.; Stephan, R. (Elsevier, 2020)
This study was conducted to determine the distribution of antimicrobial resistance among Escherichia coli isolated from feces of healthy dromedary camels in Kenya. A total of 162 fecal samples were cultivated for E. coli. Samples were also subcultivated to detect E. coli with extended-spectrum ß-lactamases (ESBLs). Antimicrobial susceptibility testing (AST) was performed by disk diffusion using a panel of 16 antimicrobials. In addition, isolates were screened for the presence of the plasmid-mediated colistin resistance genes mcr-1 to mcr-5. Samples from 20 (12.4%) of the camels contained antimicrobial resistant (AMR) E. coli, and 85% of the AMR isolates were multidrug resistant (MDR). The highest frequency of resistance was observed to tetracycline (11.7%), followed by ampicillin and streptomycin (both 10.5%), and sulfamethoxazole/trimethoprim (9.9%). Two (1.2%) of the isolates showed intermediate resistance to cefazolin and streptomycin, respectively. All the isolates were susceptible to amoxycillin/clavulanic acid, ciprofloxacin, fosfomycin, aztreonam and kanamycin, and 86.4% of the isolates were susceptible to all 16 antimicrobials used in this study. The prevalence of fecal carriage of ESBL producing E. coli was 0.6%. PCR and amplicon sequencing showed that the ESBL producer belonged to E. coli phylogenetic group A, sequence type (ST) 48, and harbored blaCTX-M-15. None of the isolates contained mcr genes. The results indicate that dromedary camels in Kenya may be reservoirs of AMR E. coli, including ESBL producers, that could potentially be transmitted to humans by direct contact or via the food chain.